"Mapping Potential Hazards: Job Safety Analysis in Lathe Companies" - Dewantari, Nustin Merdiana; Hartono, Tri Ardhi; Taqdisillah, Creavilian; Oscar, Samuel; Ilyasa, Isqy; Trenggonowati, Dyah Lintang (Journal of Systems Engineering and Management, 2024)
The industrial development in Indonesia has brought significant positive impacts, including an increase in the workforce and income. However, this growth also brings negative impacts, especially in the steel fabrication sector, where the risk of workplace accidents increases due to direct interaction with heavy equipment. This research utilizes the Job Safety Analysis (JSA) method to identify potential hazards and develop risk control measures at various workstations: Cutting, Drilling, Welding, and Turning. The JSA approach is systematically used to evaluate each stage of work activity and identify potential hazards that may arise. The research findings indicate that each workstation has specific risks that require appropriate control measures. For example, in the Cutting station, the risk of exposure to heat sparks can be minimized by using protective clothing and face shields. Similarly, in the Drilling station, the use of lifting aids is recommended to reduce the risk of back or muscle injuries.